The interplay between hormonal vitamin D and lipopolysaccharide signaling on human neutrophil transcriptional responses - Ismailova, Aiten; Salehi-Tabar, Reyhaneh; Ismailova, Nailya; Dumas, Olivia; Saliba, James; Blank, Volker; White, John H. (Frontiers in Immunology, 2025)
IntroductionBiologically active vitamin D (1,25-dihydroxyvitamin D or 1,25D) has emerged as a key regulator of human innate immunity. 1,25D signaling in macrophages strongly induces the expression of neutrophil chemoattractants, such as IL-8/CXCL8. Meta-analysis of vitamin D-regulated expression profiles has suggested that 1,25D may regulate granule formation in granulocytic cells. Here, we have examined the effects of 1,25D signaling on human neutrophil gene expression, alone and in combination with the inflammatory signal lipopolysaccharide (LPS). These studies are of interest because, whereas 1,25D signaling boosts innate immunity, it is anti-inflammatory.Methods and resultsWe determined the effects of 1,25D alone and in combination with LPS on gene expression of primary human neutrophils by RNAseq. LPS did not affect or slightly enhanced the expression of several well-characterized 1,25D-target genes, but strongly suppressed that encoding the 1,25D catabolic enzyme CYP24A1. Chromatin immunoprecipitation (ChIP) assays revealed that 1,25D-dependent vitamin D receptor (VDR) binding to the major CYP24A1 enhancer was eliminated in neutrophils treated with LPS, whereas binding to other 1,25D-target genes was unaffected. Notably, LPS induced binding of transcriptional repressors MAFF and BACH1 to the major CYP24A1 enhancer region. In other studies, pathway analyses revealed that 1,25D suppressed LPS-induced genes encoding inflammatory proteins. In addition, RNAseq and confirmatory RT/qPCR studies revealed that 1,25D, both on its own and in combination with LPS, increased mRNA expression of genes encoding antimicrobial components of secretory granules, including that encoding cathelicidin antimicrobial peptide (CAMP). Consistently, exposure of neutrophils to 1,25D enhanced bacterial killing, as revealed by a 20-25% reduction in E. coli colonies incubated with 1,25D-treated neutrophil conditioned media. The increased bacterial killing by 1,25D is mediated by 1,25D-induced secretion of cathelicidin, as an antibody against LL-37, the active form of cathelicidin, blocked antimicrobial activity.DiscussionCollectively, the data suggest that LPS prolongs vitamin D signaling by suppressing expression of the 1,25D catabolic enzyme CYP24A1. 1,25D signaling in the presence of LPS attenuates the expression of several genes associated with LPS inflammatory responses, whereas 1,25D in the absence or presence of LPS enhances the release of antibacterial proteins secreted by neutrophils in response to infection.